2009
DOI: 10.1128/aac.00316-09
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and Effect of Caspofungin on Biofilm Structure of Candida Species Bloodstream Isolates

Abstract: Candida biofilms are microbial communities, embedded in a polymeric matrix, growing attached to a surface, and are highly recalcitrant to antimicrobial therapy. These biofilms exhibit enhanced resistance against most antifungal agents except echinocandins and lipid formulations of amphotericin B. In this study, biofilm formation by different Candida species, particularly Candida albicans, C. tropicalis, and C. parapsilosis, was evaluated, and the effect of caspofungin (CAS) was assessed using a clinically rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 51 publications
4
43
0
Order By: Relevance
“…This phenomenon has subsequently been described with other echinocandins and other Candida species (Chamilos et al, 2007;Fleischhacker et al, 2008;Melo et al, 2007). This effect appears to be species-, strain-and echinocandin-specific (Chamilos et al, 2007;Ferreira et al, 2009;Melo et al, 2007;Miceli et al, 2009a, b) and associated with chitin accumulation and ultrastructural alterations (Bizerra et al, 2011); however, the clinical significance of the PE remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has subsequently been described with other echinocandins and other Candida species (Chamilos et al, 2007;Fleischhacker et al, 2008;Melo et al, 2007). This effect appears to be species-, strain-and echinocandin-specific (Chamilos et al, 2007;Ferreira et al, 2009;Melo et al, 2007;Miceli et al, 2009a, b) and associated with chitin accumulation and ultrastructural alterations (Bizerra et al, 2011); however, the clinical significance of the PE remains unclear.…”
mentioning
confidence: 99%
“…Depending on the geographical region, Candida tropicalis ranks from the second to the fourth leading cause of invasive candidiasis (Bassetti et al, 2006;Nucci et al, 2010;Pfaller et al, 2008;Tan et al, 2010). Multiple studies of echinocandins against most C. albicans biofilms have shown them to be effective at concentrations of 2 mg ml 21 or less (Bachmann et al, 2002;Cocuaud et al, 2005;Ferreira et al, 2009;Jacobson et al, 2008Jacobson et al, , 2009Kuhn et al, 2002;Miceli et al, 2009a). However, a paradoxical effect (PE) of echinocandins against C. albicans biofilms treated with high concentrations of caspofungin (CFG) has been described (Stevens et al, 2004).…”
mentioning
confidence: 99%
“…As a result of greater use of implanted medical devices than before, microbes in biofilm display increased resistance towards biocides; antibiotic chemotherapy as well decreased susceptibility to the host defense mechanisms (9, 10). Recent evidences have revealed that in more than 65 % microbial infection, biofi lms have critical role in infections and diseases associated biofilm and are becoming increasingly more diffi cult to treat (11). Candida is an important human fungal fl ora causing nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm-associated organisms can also elicit disease processes by detachment of individual cells or aggregates of cells resulting in bloodstream infections, by production of endotoxin, or by providing a niche for the development of antibioticresistant organisms. [1][2][3] Approximately 250000 cases of intravascular catheter-related bloodstream infections occur in the United States each year, resulting in a mortality of between 12-25% with an estimated cost of treatment per episode of approximately $25000. [3][4][5][6][7][8][9][10] The standard management of catheter-related infection involves decisions regarding removal of the catheter and the administration of appropriate antibiotics.…”
Section: Introductionmentioning
confidence: 99%